The Role of Oxidative Stress Markers (MDA and SOD) in the Abortion with Diabetic Women in Iraq - Naghma Abdulsahib Hussein (Indonesian Journal on Health Science and Medicine, 2026)
General Background: Spontaneous abortion is a common pregnancy complication with higher occurrence among women with diabetes mellitus, where oxidative imbalance and micronutrient deficiency are implicated. Specific Background: Oxidative stress markers such as malondialdehyde (MDA) and antioxidant enzymes like superoxide dismutase (SOD), together with vitamin D₃ status and glycemic indices, are associated with adverse pregnancy outcomes. Knowledge Gap: However, the interrelationship between oxidative stress, antioxidant defense, glycemic control, and vitamin D₃ levels in diabetic women experiencing miscarriage remains insufficiently characterized. Aims: This study assessed MDA and SOD levels and their association with glycemic parameters and vitamin D₃ in diabetic women with spontaneous abortion. Results: A case–control analysis of 80 women revealed significantly higher random blood sugar, HbA1c, and MDA levels, alongside significantly lower vitamin D₃ levels in patients compared to controls (p < 0.001). SOD activity was significantly altered, indicating disrupted antioxidant defense. HbA1c showed strong positive correlation with MDA (r = 0.847) and negative correlations with SOD (r = −0.748) and vitamin D₃ (r = −0.702). Novelty: This study demonstrates integrated correlations between oxidative stress biomarkers, antioxidant imbalance, glycemic dysregulation, and vitamin D₃ deficiency in diabetes-related miscarriage. Implications: These findings suggest that combined monitoring of oxidative stress markers, glycemic indices, and vitamin D₃ status may support improved understanding and management of miscarriage risk in diabetic women. Highlights:• Elevated lipid peroxidation and glucose indicators observed in affected patients• Reduced micronutrient status linked with altered antioxidant enzyme activity• Strong correlations identified among metabolic, oxidative, and nutritional parameters Keywords: Oxidative Stress, Malondialdehyde, Superoxide Dismutase, Diabetes Mellitus, Vitamin D3